The Association between Vitamin B12 Deficiency and Metformin Therapy in Libyan Diabetic Patients - Nagat Elbarghathi; Hoda Ahwaide; Narmin Elbouri (AlQalam Journal of Medical and Applied Sciences, 2025)
Metformin is the first line treatment of diabetic hyperglycaemia. However, numerous studies have shown that long-term use of metformin can result in a vitamin B12 deficiency. In this study, we sought to assess the prevalence of vitamin B12 deficiency in diabetic patients taking metformin on a long-term basis as well as the association between vitamin B12 deficiency and diabetic neuropathy. Across sectional study was conducted on 143 Libyan diabetic patients attending endocrinology outpatient diabetic centre in Benghazi, who are on metformin for at least 6 months, and eligible to the inclusion criteria. Data on metformin intake and confounding variables were collected from questionnaires. Serum vitamin B12 levels were estimated, and vitamin B12 deficiency was defined as serum B12 less than 196pg/ml. Data analysis was performed using the statistical package for social sciences (SPSS) version 28. The study involved 143 patients, with a majority being women (50.3%) and men (49.7%). The mean duration of diabetes was 10.52 ± 7.260 years. The mean daily dose of metformin was 1435.42 ± 377.766 mg for females and 1495.77 ± 392.678 mg for males. The mean duration of metformin intake was 7.93 ± 5.859 years for females and 7.34 ± 5.780 years for males. The mean serum vitamin B12 level was 469.78 ± 233.477 pg/mL, with males having non-significantly higher levels than females. 59.2% of male patients had vitamin B12 levels ≤420 pg/mL, while 51.4% of female patients had levels ≤420 pg/mL. Nevertheless, no patient had a vitamin B12 deficit. No significant correlation was observed between serum vitamin B12 levels with metformin dose, duration of action, or patient characteristics. Despite the high prevalence of peripheral neuropathy (36.4%), there was no significant difference in B12 levels between patients with and without neuropathy. الميتفورمين هو العلاج الأول لفرط سكر الدم لدى مرضى السكري. ومع ذلك، أظهرت العديد من الدراسات أن الاستخدام طويل الأمد للميتفورمين يمكن أن يؤدي إلى نقص في فيتامين ب12. في هذه الدراسة، سعينا لتقييم انتشار نقص فيتامين ب12 لدى مرضى السكري الذين يتناولون الميتفورمين على أساس طويل الأمد، بالإضافة إلى العلاقة بين نقص فيتامين ب12 واعتلال الأعصاب السكري. تم إجراء دراسة مقطعية على 143 مريضًا ليبيًا مصابًا بالسكري يترددون على مركز السكري الخارجي لأمراض الغدد الصماء في بنغازي، والذين يتناولون الميتفورمين لمدة لا تقل عن 6 أشهر، ويستوفون معايير الإدراج. تم جمع بيانات حول تناول الميتفورمين والمتغيرات المؤثرة من الاستبيانات. تم تقدير مستوى فيتامين ب12 في المصل،. وتم تعريف نقص فيتامين ب12 بأنه مستوى أقل من 196 بيكوغرام/مل.تم إجراء تحليل البيانات باستخدام الحزمة SPSS الاصدار 28. تمثل النساء (50.3%) والرجال (49.7%). كان متوسط مدة الإصابة بالسكري 10.52 ± 7.260 سنوات. كان متوسط الجرعة اليومية من الميتفورمين 1435.42 ± 377.766 ملغ للإناث و1495.77 ± 392.678 ملغ للذكور. كان متوسط مدة تناول الميتفورمين 7.93 ± 5.859 سنوات للإناث و7.34 ± 5.780 سنوات للذكور. كان متوسط مستوى فيتامين ب12 في المصل 469.78 ± 233.477 بيكوغرام/مل، مع وجود مستويات أعلى غير ذات دلالة إحصائية لدى الذكور مقارنة بالإناث. كانت نسبة 59.2% من المرضى الذكور لديهم مستويات فيتامين ب12 ≤420 بيكوغرام/مل، بينما كانت النسبة لدى الإناث 51.4% لديهم مستويات ≤420 بيكوغرام/مل. ومع ذلك، لم يكن هناك أي مريض يعاني من عجز في فيتامين ب12. لم يتم ملاحظة أي ارتباط ذو دلالة إحصائية بين مستويات فيتامين ب12 في المصل مع جرعة الميتفورمين أو مدة العمل أو خصائص المرضى الأخرى. على الرغم من الانتشار العالي للاعتلال العصبي المحيطي (36.4%)، لم يكن هناك فرق ذو دلالة إحصائية بين مستويات فيتامين ب12 في المصل مع جرعة الميتفورمين أو مدة العمل أو خصائص المرضى الأخرى. على الرغم من الانتشار العالي للاعتلال العصبي المحيطي (36.4%)، لم يكن هناك فرق ذو دلالة إحصائية بين مستويات B12 لدى المرضى الذين يعانون من اعتلال الأعصاب والذين لا يعانون منه. B12 لدى المرضى الذين يعانون من اعتلال الأعصاب والذين لا يعانون منه